1998
DOI: 10.1007/bf02443445
|View full text |Cite
|
Sign up to set email alerts
|

Design of a synthetic adhesion protein by grafting RGD tailed cyclic peptides on bovine serum albumin

Abstract: SummaryA synthetic adhesion protein was designed by chemical grafting of the RGD tailed cyclic peptide cyclo[-D-Val-ArgGly-Asp-Glu(-EAhx-Tyr-Cys-NH~)-] on the carrier protein bovine serum albumin (BSA). The cyclic conformation of the RGD motif grafted on the protein mimics the conformation of the motif displayed in native adhesion proteins such as fibronectin. The adhesion of the cells on polystyrene coated with the conjugate BSA-peptide was similar or even better than the one obtained when the proadhesive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 17 publications
1
18
0
1
Order By: Relevance
“…It is of much interest to examine the conformation of the RGD-peptide, which once immobilised to titanium surfaces, will be able to improve biointegration of an implant by stimulation of ECs. The cyclic peptide seems to enhance the binding (Delforge et al, 1998;Hsiong et al, 2008;Zhu et al, 2009). A difference in EC cell coverage and proliferation on titanium surfaces by means of the structure of RGD peptides, which could be shown in our study, has not been investigated.…”
Section: Discussionmentioning
confidence: 67%
“…It is of much interest to examine the conformation of the RGD-peptide, which once immobilised to titanium surfaces, will be able to improve biointegration of an implant by stimulation of ECs. The cyclic peptide seems to enhance the binding (Delforge et al, 1998;Hsiong et al, 2008;Zhu et al, 2009). A difference in EC cell coverage and proliferation on titanium surfaces by means of the structure of RGD peptides, which could be shown in our study, has not been investigated.…”
Section: Discussionmentioning
confidence: 67%
“…Specifically, it has been found that conformation of RGD‐containing peptides affect cell binding and can control the specificity to an integrin. In addition, cyclic‐RGD peptides immobilized on the material surfaces have a more effective promotion on cell attachment and a higher in vivo stability compared to the linear‐based peptides . It may benefit from the decreased structural flexibility exerted by the ring .…”
Section: Characteristics Of Peptide Immobilized Onto the Matrix Surfacementioning
confidence: 99%
“…In addition, cyclic-RGD peptides immobilized on the material surfaces have a more effective promotion on cell attachment and a higher in vivo stability compared to the linear-based peptides. 19,[39][40][41] It may benefit from the decreased structural flexibility exerted by the ring. 42 Moreover, this rigidity stabilizes the Asp side chain carboxylic acid, which helps avoid proteases attack when orientating itself in a suitable position.…”
Section: Sequence Of Peptide Immobilized Onto the Matrix Surfacementioning
confidence: 99%
“…En effet, van der Pluijm et al [50] et Delforge et al [51] ont montré une augmentation de l'attachement cellulaire en utilisant leurs peptides cycliques comparativement à des peptides linéaires. Par ailleurs, le peptide cyclique c(-RGDfX-) pour lequel l'acide aminé D suit la fonction aspartate induit une conformation de la séquence RGD telle que celle-ci est mieux reconnue par les intégrines av et présente une affinité très largement réduite vis-à-vis des récepteurs plaquettaires aIIbb3 [52,53].…”
Section: Protéines Ou Peptides ?unclassified